The Bases of Social Motivation - Legkauskas, Visvaldas (Sociologija. Mintis ir veiksmas, 2004)
The present article is aimed at specifying bases of social motivation, defining the basic social needs and interrelations among them. A basic social need is defined as such a need, which is not a product of culture, but constitutes a pre-condition for formation of a social group, which in turn creates the culture itself. Three such conditions are identified: attention of group members to each other, positive evaluation of each other, and care for each others well-being. A person experiences these conditions as needs for attention, esteem, and care. These three needs are interrelated in a hierarchical manner. The need for attention is the least important, while the need for care is the most important, as satisfaction of this need is both necessary and sufficient condition for formation and survival of a social group. Also, compared to the needs for attention and esteem, satisfaction of the need for care requires the most complex means.Despite of such subordination of the need for attention and the need for esteem to satisfaction of the need for care, both needs for attention and esteem should be considered as separate needs, as satisfaction of these needs constitutes pre-condition for satisfaction of the need for care and hence these needs acquire an independent motivational value.
Keywords: social motivation; social needs; attention to other; positive evaluation; care